2023
DOI: 10.3389/fimmu.2023.1194671
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and cellular responses to repeated COVID-19 exposure in multiple sclerosis patients receiving B-cell depleting therapies: a single-center, one-year, prospective study

Abstract: Multiple sclerosis patients treated with anti-CD20 therapy (aCD20-MS) are considered especially vulnerable to complications from SARS-CoV-2 infection due to severe B-cell depletion with limited viral antigen-specific immunoglobulin production. Therefore, multiple vaccine doses as part of the primary vaccination series and booster updates have been recommended for this group of immunocompromised individuals. Even though much less studied than antibody-mediated humoral responses, T-cell responses play an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 91 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…Some authors showed a severely impaired humoral response in immunodepressed and immunosuppressed patients even after several exposures of vaccine, but with a strong T-cell response. Evaluating both humoral and cellular responses in vaccinated patients with immune system failure appeared to be a good strategy to better assess individual immune protection [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors showed a severely impaired humoral response in immunodepressed and immunosuppressed patients even after several exposures of vaccine, but with a strong T-cell response. Evaluating both humoral and cellular responses in vaccinated patients with immune system failure appeared to be a good strategy to better assess individual immune protection [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%